2011
DOI: 10.1080/01490451.2011.581325
|View full text |Cite
|
Sign up to set email alerts
|

Copper Biogeochemistry: A Cornerstone in Aerobic Methanotrophic Bacterial Ecology and Activity?

Abstract: Two distinct enzymatic pathways are implicated in the key step whereby methane is converted to methanol by the aerobic methane oxidizing bacteria (methanotrophs). These two enzymes, soluble and particulate methane monooxygenases (sMMO and pMMO, respectively), are evolutionarily unrelated. However, the activities of these enzymes are tightly linked to copper, which is central to the switch responsible for regulating MMO expression. When bioavailable copper exceeds a certain threshold relative to cell biomass, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 152 publications
1
11
1
Order By: Relevance
“…Thus, more methane is available for methanotrophs in the mesotelm. Community composition based on 16S rRNA gene sequences (27) and phylogenetic assignments of pmoA and mmoX genes (see Table S1 in the supplemental material) both showed that members of the Methylocystaceae (type II methanotrophs) were more abundant than the Methylococcaceae (type I methanotrophs) in our samples, in corroboration with observations in other northern peatlands (54)(55)(56). This observation contrasts with the dominance of Methylococcaceae found in metagenomes from the Arctic fen and mineral soils (11).…”
Section: Resultscontrasting
confidence: 54%
See 1 more Smart Citation
“…Thus, more methane is available for methanotrophs in the mesotelm. Community composition based on 16S rRNA gene sequences (27) and phylogenetic assignments of pmoA and mmoX genes (see Table S1 in the supplemental material) both showed that members of the Methylocystaceae (type II methanotrophs) were more abundant than the Methylococcaceae (type I methanotrophs) in our samples, in corroboration with observations in other northern peatlands (54)(55)(56). This observation contrasts with the dominance of Methylococcaceae found in metagenomes from the Arctic fen and mineral soils (11).…”
Section: Resultscontrasting
confidence: 54%
“…The abundance of type II methanotrophs in peatlands could be explained by the fact that the Methylocystaceae (Methylocystis) were shown to be acidophilic or acidotolerant, while no acidophilic representatives are known among type I methanotrophs (57,58). In addition, copper limitation in nutrient-poor ombrotrophic peatlands may also favor non-copper-dependent type II methanotrophs (56). None of the pmoA gene sequences retrieved from our metagenomes were grouped with the Methylacidiphilaceae-like pmoA gene sequences (data not shown), consistent with SSU rRNA gene-based amplicon sequencing results indicating that verrucomicrobial methanotrophs have not yet been detected in acidic peatlands (27,59).…”
Section: Resultsmentioning
confidence: 99%
“…However, biological weathering involves biochemical and physical processes, such as the secretion of organic acids (McMaster 2012;Neaman et al 2005;Valix et al 2001), complexation (Koretsky 2000;Lian et al 2008b), oxidation-reduction (Brown et al 2003;Shelobolina et al 2012;Shock 2009) and bio-mechanical action (Bonneville et al 2011;Chen et al 2000). Some materials secreted by organisms has made it easy to identify associations between biological enzymes and mineral weathering (Fru 2011;Xiao et al 2012a) and to determine whether organisms can affect the weathering rate through enzyme secretion. Carbonic anhydrase (CA) is widely distributed in animal cells (Jackson et al 2007;Supuran and Scozzafava 2007), plant cells (Bradfield 1947;Moroney et al 2001;Sunderhaus et al 2006) and microorganisms (Bahn et al 2005;HewettEmmett and Tashian 1996;Smith and Ferry 2000).…”
Section: Introductionmentioning
confidence: 98%
“…Some MOB utilize special mechanisms to regulate their Cu homeostasis, also in response to Cu toxicity at high levels. The chalkophore methanobactin, the extracellular component of a Cu acquisition system, binds Cu with high affinity and specificity and is able to increase the bioavailable Cu fraction by dissolving Cu from soluble, mineral, and humic sources, but open questions about its role still remain 13,14 . It has recently been proposed that methanobactin works in concert with a protein called MmoD to modulate the Cu-switch of sMMO and pMMO 15 , however, other proteins are also involved in the Cu or Cu-methanobactin uptake and/or the Cu-switch in MOB 1620 .…”
Section: Introductionmentioning
confidence: 99%